Characterization and reactivity of VMgO catalysts prepared by wet impregnation and sol–gel methods. Issue 9 (2nd September 2018) - Slyemi, Samira; Barama, Siham; Barama, Akila; Blanchard, Juliette; Messaoudi, Hassiba; Casale, Sandra; Calers, Christophe
ABSTRACT: This paper reports the study of physicochemical, surface, and catalytic properties of two series of VMgO catalysts prepared by two different methods: wet impregnation and sol–gel. The characterizations of the elaborated materials were performed using N2 -sorption (Brunauer, Emmett and Teller (BET)), X-ray diffraction, Raman, transmission electron microscopy–energy-dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy analyses. The catalytic properties of the elaborated materials were investigated in the isopropanol decomposition reaction to determine their acid–base character and in the selective oxidation of n -butane to evaluate their dehydrogenation properties. The preparation method and vanadium content strongly affected the properties of our materials. The sol–gel method leads to smaller crystallite size, higher specific surface area, and uniform particle distribution compared to the impregnation one. Both impregnation and SG solids promote the formation of acetone, which is related to the presence of strong basic sites (O 2− species) on the catalytic exposed surface. The more pronounced basic character was obtained through the SG samples. The sol–gel samples exhibited the highest catalytic activity and C4-olefin selectivity in the partial oxidation of n -butane. Whatever the preparation procedure, the nature of surface oxygen species plays an important role in the orientation of catalytic performances.